Factors associated with knowledge, attitudes and practices about COVID-19 in hemodialysis patients - Christopher Rivera-Santos, Alexis Henry (2023)
Introduction: During the COVID-19 pandemic, several shortcomings in the health system were evidenced, particularly in the first level of care sector, being thechronic renal population one of the most affected. Objectives: To determine the association between epidemiological factors and the “knowledge, attitudes and practices” of the population with chronic kidney disease (CKD) on hemodialysis in the province of Huancayo, Peru, during 2022.Methods: Cross-sectional analytical observational study conducted at the Ramiro Prialé Prialé National Hospital, Huancayo, Junín, between January and March2022. A data collection form was administered that assessed and quantified the level of “knowledge, attitudes and practices” of the patients. The chi-square test was applied to evaluate the association. Results: Seventy-six patients with chronic kidney disease (CKD) on hemodialysis were studied. Most of the population was older adults (51.32 %), had higher education (40.78 %) and were from the province of Huancayo (73.68 %). The main cause of CKD was arterial hypertension (40.7%), and 19.7% had diabetes mellitus as a history. A statistically significant association was found between the level of education and the level of knowledge about COVID-19 in hemodialysis patients (p<0.05). No correlation was found between the variables age and time on hemodialysis with respect to the “knowledge, attitudes and practices” under COVID-19 (p<0.05). Conclusion: There was an association between the level of education and the level of knowledge about COVID-19 in the hemodialysis population.